Możliwości stosowania ubezpieczenia do finansowania skutków ryzyka choroby - Kawiński, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this paper is to point out conditions and potential problems when using insurance method to finance results of sickness risk. The requirements based on the concept of insurability were confronted with citizens' expectations in case of sickness risk. The analysis of potential problems was made in the context of general and selective coverage. That allows coming to a conclusion that a universal coverage is merely possible when using insurance method and that much pore promising is the usage of insurance to assure selective coverage. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 156-165